Prototype Web-Based Surveillance and Management Reporting System for Public Street Lighting - Santika, Maria Enggar; Wirayuda, Samuel Tristan; Setyawan, Lukas Bambang (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2024)
The growing global population and rapid urbanization have escalated the demand for smart city technologies that promote sustainability and efficient resource management, particularly through IoT-based data processing systems. Efficient urban infrastructure management, such as public street lighting, is crucial to meet these demands. However, many local governments continue to rely on manual inspections, which are inefficient and costly, underscoring the need for automated, real-time monitoring solutions that improve reliability and reduce operational expenses. This research presents a system that automates streetlight control based on predefined schedules and reports any malfunctions to a central database. The system leverages an Arduino Nano as the main controller, an RTC (Real-Time Clock) for timing, a GSM Shield SIM900 for communication, and solar panels as an energy source. Experimental results demonstrate that the lighting system operates reliably according to the specified schedule. Experimental results show that the lighting system operates according to the specified schedule and the SIM900 module sends data from the sensors to the website in real-time.